2022
DOI: 10.1007/s13365-021-01029-0
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal, virological, and serological assessment of hospitalized COVID-19 patients

Abstract: Here we described the virological and serological assessment of 23 COVID-19 patients hospitalized and followed up in Milan, Italy, during the first wave of COVID-19 pandemic. Nasopharyngeal (NPS), anal swabs, and blood samples were collected from 23 COVID-19 patients, at hospital admission, and periodically up to discharge, for a median time of 20 days (3–83 days). RNA was isolated and tested for SARS-CoV-2 by qRT-PCR; anti-SARS-CoV-2 IgM and IgG antibody titers were evaluated in serum samples by ELISA. SARS-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…This result is unique, as only very few studies have previously reported test data from intestinal organs. Furthermore, in the few previously reported studies, nondetectable anti-SARS-CoV-2 antibody levels were shown 45,46 .…”
Section: Discussionmentioning
confidence: 88%
“…This result is unique, as only very few studies have previously reported test data from intestinal organs. Furthermore, in the few previously reported studies, nondetectable anti-SARS-CoV-2 antibody levels were shown 45,46 .…”
Section: Discussionmentioning
confidence: 88%
“…It is worth mentioning that the proposed course of SARS-CoV-2 infection could start in upper respiratory tract infection (mainly as respiratory droplets), continue in lower respiratory tract infection (mainly as pulmonary infection) , followed by viremia and diffusion to other target organs (including the gastrointestinal tract), the latter being very important as it is associated with the theory that the spread of SARS-CoV-2 in hospitals and nursing homes could occur through fecal contamination, involving health personnel in the infection, who are usually able to protect themselves from droplets, wear masks, but less easily during direct care and hygiene of patients, where people are generally bedridden and not autonomous in the handling of their stools, so it should be reiterated in the proper use of personal protection equipment 11 .…”
Section: Letter To Editor / Carta Al Editormentioning
confidence: 99%